The deubiquitinase USP21 maintains the stemness of mouse embryonic stem cells via stabilization of Nanog - Jiali Jin (Nature Portfolio, 2016)
Nanog regulates embryonic stem cell (ESC) pluripotency but what controls Nanog protein stability is unclear. Here, the authors show that in mouse ESCs, Nanog protein is ubiquitinated and stabilized by the deubiquitinase USP21, which in turn is regulated by extrinsic signals, STAT3 and ERK.